Sugamo Diary - Sasakawa, Ryôichi (Hurst & Company, 2010)
This collection of writings by Ryoichi Sasakawa is presented in two parts: daily logs covering a year of incarceration in Sugamo Prison, where he was detained as a Class A war-crimes suspect from 1945 to 1946, followed by letters sent between 1945 and 1948, mostly to family members and political associates.